Comparison of Patient Outcomes following Implantation of Trifocal and Extended Depth of Focus Intraocular Lenses: A Systematic Review and Meta-Analysis - Yining Guo; Yinhao Wang; Ran Hao; Xiaodan Jiang; Ziyuan Liu; Xuemin Li (Journal of Ophthalmology)
Purpose. The purpose is to compare the outcomes of implantation of trifocal intraocular lenses (TIOLs) and extended depth of focus (EDOF) intraocular lenses (IOLs). Methods. A comprehensive search of PubMed, Cochrane Library, EMBASE, and ClinicalTrial.gov was conducted in March 2020 to identify relevant studies. A meta-analysis of the results was performed. Patients implanted with EDOF IOLs or TIOLs in previous studies were included. The primary outcomes of the study were uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA), and defocus curve. Results. TIOLs and EDOF IOLs provided comparable binocular UDVA (MD = -0.01, 95% CI: -0.04, 0.03, logMAR). However, EDOF IOLs provided better UIVA (MD: -0.08, 95% CI: -0.14, -0.01, logMAR) and worse UNVA (MD: 0.10, 95% CI: 0.06, 0.14, logMAR) than TIOLs. Fewer patients achieved spectacle independence after implantation of EDOF IOLs (RR: 0.74, 95% CI: 0.63, 0.87) than after implantation of TIOLs, especially for near vision (RR = 0.82, 95% CI: 0.68, 0.99). There was no statistically significant difference in contrast sensitivity (CS) under photopic or mesopic conditions with both IOLs. Patient satisfaction after implantation of both IOLs was high. Conclusion. EDOF IOLs and TIOLs provide comparable distance vision. However, EDOF IOLs provide better intermediate vision and worse near vision than TIOLs. The advantages of EDOF IOLs over TIOLs in terms of CS, aberrations, and visual disturbance are not significant. Patients are satisfied with both types of IOLs.